2012
DOI: 10.4300/jgme-d-11-00280.1
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Test of Residents' Ethics Knowledge for Pediatrics (TREK-P)

Abstract: Background Professionalism is one of the Accreditation Council for Graduate Medical Education's core competencies. Residency programs must teach residents about ethical principles, which is an essential component of professionalism. Objectives We aimed to formally develop a valid and reliable test of ethics knowledge that effectively discriminated among learners in pediatric residency training and to improve methods for measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…Forty respondents (40%) scored 20 or higher, thereby achieving the level of high performance reported in previous work (Kesselheim et al 2012). Post hoc analysis of this high-performing subgroup revealed that scoring 20 or above on the TREK-P was more common (55% vs. 33%, p D 0.04) among ECs who received salary support than among ECs without salary support and among ECs with, as compared to those without, formal training (47% vs. 22%, p D 0.02).…”
Section: Trek-p Performancementioning
confidence: 55%
See 4 more Smart Citations
“…Forty respondents (40%) scored 20 or higher, thereby achieving the level of high performance reported in previous work (Kesselheim et al 2012). Post hoc analysis of this high-performing subgroup revealed that scoring 20 or above on the TREK-P was more common (55% vs. 33%, p D 0.04) among ECs who received salary support than among ECs without salary support and among ECs with, as compared to those without, formal training (47% vs. 22%, p D 0.02).…”
Section: Trek-p Performancementioning
confidence: 55%
“…Because of a skew in the distribution of TREK-P scores in this sample, the nonparametric Wilcoxon rank sum test (Kruskal-Wallis test with >2 comparison groups) was used to compare the distribution of TREK-P scores between the following groups: (1) CHA hospitals versus COTH hospitals; (2) formal training versus informal training; (3) high volume (>10 per year) versus low volume (10 or fewer per year) consult services; (4) budget; (5) salary support; and (6) geographic region. Post hoc analyses compared these same groups for the difference in proportion having TREK-P scores 20, a marker of particularly high performance identified in earlier work (Kesselheim et al 2012). …”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations